2010
DOI: 10.3858/emm.2010.42.10.068
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 induces expression of zinc-finger protein 143 in colon cancer cells through phosphatidylinositide 3-kinase and reactive oxygen species

Abstract: Expression of zinc-finger protein 143 (ZNF143), a human homolog of the Xenopus transcriptional activator protein Staf, is induced by various DNA-damaging agents including etoposide, doxorubicin, and γ-irradiation. ZNF143 binds to cisplatin-modified DNA, and its levels are increased in cancer cells that are resistant to anticancer drugs, including cisplatin, suggesting that it plays a role in carcinogenesis and cancer cell survival. However, the mechanism of ZNF143 induction in cancer cells remains unclear. Bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…We therefore presume that the homeobox family TFs highly expressed by idNK cells may contribute to their immaturity. ZNF143 can be induced by IGF‐1 . Interestingly, we previously reported that IGF‐1 is critical for human NK‐cell cytotoxicity , which is consistent with the observed higher Znf143 expression in mpNK cells that are known to exert cytotoxic activity.…”
Section: Discussionsupporting
confidence: 87%
“…We therefore presume that the homeobox family TFs highly expressed by idNK cells may contribute to their immaturity. ZNF143 can be induced by IGF‐1 . Interestingly, we previously reported that IGF‐1 is critical for human NK‐cell cytotoxicity , which is consistent with the observed higher Znf143 expression in mpNK cells that are known to exert cytotoxic activity.…”
Section: Discussionsupporting
confidence: 87%
“…The control cell lines (HCT116 sh-control) and cell lines stably expressing ZNF143 shRNA (HCT116 sh-ZNF143) or GIPC shRNA (HCT116 sh-GIPC) were selected in 10 μg/ml puromycin dihydrochloride for 2 weeks and maintained in growth medium containing 1 μg/ml puromycin dihydrochloride. To avoid clonal variation, the individual clones for each stable cell line produced by infection were pooled (Choi et al, 2010;Paek et al, 2010).…”
Section: Cell Culturementioning
confidence: 99%
“…ZNF143 has been implicated in DNA-damage responses and the resistance of cancer cells to cisplatin, suggesting that the protein plays a role in carcinogenesis and cancer cell survival (Ishiguchi et al, 2004;Wakasugi et al, 2007). Previously, we showed that IGF-1 induced ZNF143 expression through reactive oxygen species (ROS) and phosphatidylinositide 3-kinase (PI3-kinase)-linked signaling pathways (Paek et al, 2010). However, several questions remain to be answered, such as how IGF-1R induces ZNF143 expression.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, ZNF143 has been suggested to play roles in various activities . Previous studies demonstrated that ZNF143 is involved in the cell cycle, cell viability, and drug resistance . Furthermore, the knockdown of ZNF143 expression by small interfering RNA (siRNA) downregulated the expression of various cell cycle/DNA replication‐associated genes and inhibited the progression of the cell cycle and tumor cell growth .…”
mentioning
confidence: 99%
“…(2) Previous studies demonstrated that ZNF143 is involved in the cell cycle, cell viability, and drug resistance. (3)(4)(5)(6)(7)(8)(9)(10)(11) Furthermore, the knockdown of ZNF143 expression by small interfering RNA (siRNA) downregulated the expression of various cell cycle/DNA replication-associated genes and inhibited the progression of the cell cycle and tumor cell growth. (3) ZNF143 was also more strongly expressed in solid tumors than in adjacent non-tumor samples.…”
mentioning
confidence: 99%